(untitled) (Research, Society and Development, 2022)
The objective of this study is analyze, in the context of COVID-19, the performance of Brazilian agribusiness between 2020 and 2021. As well as identify and analyze possible negative impacts on agribusiness chains in a global context. For this purpose, a narrative literature review on the theme was conducted, with the delimitation of structured research procedures and criteria in two stages. The research points out that Brazilian agribusiness presented a comparatively better economic performance in relation to other sectors of the economy. The priority given by governments to the functioning of agrifood chains and the absence of significant interruptions in supply chains were important for this result. However, the research makes a critical analysis of some conclusions of the national literature, based strictly on economic indicators (GDP, exports, trade balance, etc.), which indicate that agribusiness was not affected by the pandemic. These studies can lead to the wrong conclusion that there were no negative impacts (or that they were not significant) for the sector. In this sense, the article lists some negative impacts on agribusiness chains resulting from isolation measures. The effects were discussed from the sector’s point of view, considering specific aspects of the products and agricultural commercialization. Finally, it proposes that further research should seek to isolate net effects of COVID-19 on the sector, highlighting the importance of this for structuring productive chains more resilient and responsive to critical moments.